1991
DOI: 10.1111/j.1440-1746.1991.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus antibody in an area endemic for hepatitis B virus and human T cell leukaemia virus

Abstract: To clarify the prevalence of concurrent infection with hepatitis C virus (HCV), hepatitis B virus (HBV) and human T cell leukaemia virus (HTLV), we measured HCV antibody in the population of a district endemic for HBV and HTLV infection. Blood samples were collected in June 1990 from 579 inhabitants of four islands of Uwa Bay in the southwest of Ehime Prefecture in Japan. Anti-HCV antibody against C100-3 protein was detected using an enzyme-linked immunosorbent assay kit (Ortho Diagnostics). Thirteen of the 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The estimated HCV prevalence was 1–1.9%. Published estimates come from a large number of blood donor (138, 143–149) and subgroup‐based studies throughout the country from 1991 to 2010 (140, 141, 145, 147, 150–184). A study of pregnant women in 1990–1994 found a prevalence of 0.3% in women <40, and 1.8% in women over 40, suggestive of the importance of historical risk factors (140).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated HCV prevalence was 1–1.9%. Published estimates come from a large number of blood donor (138, 143–149) and subgroup‐based studies throughout the country from 1991 to 2010 (140, 141, 145, 147, 150–184). A study of pregnant women in 1990–1994 found a prevalence of 0.3% in women <40, and 1.8% in women over 40, suggestive of the importance of historical risk factors (140).…”
Section: Resultsmentioning
confidence: 99%
“…Anti-HTLV-I antibody was estimated by Karpas ATLA kit (Denka Seken, enzyme immunoassay). 5 Standard control, both positive and negative were used for assays. In 2018, all assays were accomplished based on standard estimation procedures of Japan,…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of hepatitis and HTLV has been reported from different parts of Ehime prefecture and its Islands. 5 To assess more insights about prevalence of various infectious diseases, a unique mass screening system has been initiated at Ehime. This has been done by ship so that the remote islands can be enrolled in surveillance process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, HCV infection among blood donors or the general population is mostly low (1-2%) even in areas where HBV infection is endemic [Degos 1994;Bhandari and Wright, 1995;McCarthy et al, 1994;Ochi et al, 1991;Soni et al, 1993;Biltz et al, 1994]. This discrepancy between the high HBV and low HCV infection rates has been mainly attributed to a lack of introduction of HCV to the community.…”
Section: Introductionmentioning
confidence: 86%